Crop and irrigation management strategies for saline-sodic soils and waters aimed at environmentally sustainable agriculture - Qadir, Manzoor; Oster, J.D. (2004)
Irrigation has long played a key role in feeding the expanding world population and is expected to play a still greater role in the future.As supplies of good-quality irrigation water are expected to decrease in several regions due to increased municipal-industrial-agricultural competition, available freshwater supplies need to be used more efficiently.In addition, reliance on the use and reuse of saline andyor sodic drainage waters, generated by irrigated agriculture, seems inevitable for irrigation.The same applies to salt-affected soils, which occupy more than 20% of the irrigated lands, and warrant attention for efficient, inexpensive and environmentally acceptable management. Technologically and from a management perspective, a couple of strategies have shown the potential to improve crop production under irrigated agriculture while minimizing the adverse environmental impacts.The first strategy, vegetative bioremediation?a plant-assisted reclamation approach?relies on growing appropriate plant species that can tolerate ambient soil salinity and sodicity levels during reclamation of salt-affected soils.A variety of plant species of agricultural significance have been found to be effective in sustainable reclamation of calcareous and moderately sodic and saline-sodic soils.The second strategy fosters dedicating soils to crop production systems where saline andyor sodic waters predominate and their disposal options are limited.Pr oduction systems based on salttolerant plant species using drainage waters may be sustainable with the potential of transforming such waters from an environmental burden into an economic asset.Such a strategy would encourage the disposal of drainage waters within the irrigated regions where they are generated rather than exporting these waters to other regions via discharge into main irrigation canals, local streams, or rivers.Being economically and environmentally sustainable, these strategies could be the key to future agricultural and economic growth and social wealth in regions where saltaffected soils exist andyor where saline-sodic drainage waters are generated.